Performance of Auditors During the Years of the Pandemic and Contributing Factors - Budiandru Budiandru (Jurnal Akuntansi dan Pajak, 2023)
The current COVID-19 pandemic is causing the global economy to experience disruption, increasing the risk of material misrepresentation. Therefore, in providing income regarding the fairness of the audited financial statements, an auditor must have experience, professional ethics, and professionalism to achieve good auditor performance. This study aims to determine auditor experience, professional ethics, and auditor professionalism on auditor performance. The research method uses multiple linear regression with primary data and data collection using a questionnaire distributed to auditors in Jakarta, Bogor, Depok, Tangerang, and Bekasi who feel the impact of the COVID-19 pandemic with a total sample of 201 respondents. The results showed that the experience of auditors and professional auditors had a significant effect on auditor performance, while professional ethics did not affect. According to what has been determined not to act according to personal wishes, an auditor must apply professional ethics. Auditors must also improve their professionalism to get good performance even during a pandemic.